LVI and DI-SPME Combined with GC/MS and GC/MS for Volatile Chemical Profile Investigation and Cytotoxic Power Evaluation of Essential Oil and Hydrolate from Cannabis sativa L. cv. Carmagnola - Vittorio Vinciguerra; Marta Di Martile; Monica Mollica Graziano; Donatella Del Bufalo; Stefania Garzoli (Molecules, 2024)
Cannabis sativa L. is a plant that has been cultivated since ancient times thanks to its various uses. Even its extraction products, such as essential oil and hydrolate, having a varied chemical composition and rich in bioactive components, find wide use in different sectors, gathering ever-increasing interest over time. In this work, the essential oil of Cannabis sativa L. cv. Carmagnola was characterized by using Gas Chromatography/Mass Spectrometry (GC/MS) and, for the first time, the chemical profile of the hydrolate was also described through different analytical techniques such as Large-Volume Injection Gas Chromatography/Mass Spectrometry (LVI-GC/MS) and Direct Immersion-Solid Phase Microextraction-Gas Chromatography/Mass spectrometry (DI-SPME-GC/MS), in order to provide a more complete compositional profile. The results of the analyses conducted on the hydrolate highlighted a high content of α-terpineol; on the other side, in the essential oil, a prevalence of monoterpenes, with α-pinene and limonene as the characterizing components, was detected. Both matrices were also investigated to evaluate their cytotoxic activity by using a panel of cancer cell lines derived from different histotypes such as melanoma (A375, LOX IMVI), non-small cell lung cancer (H1299, A549), colon (HT29) and pancreatic (L3.6) cancer cell lines. The obtained data demonstrated that essential oil was more effective than hydrolate in terms of reduction in cell viability.